Reflexive habitus and the new obligation of choice: understanding young people's light drinking and alcohol abstinence. (9th August 2021) - Caluzzi, Gabriel; Pennay, Amy; MacLean, Sarah
ABSTRACT: This article examines how young people construct drinking and non-drinking as a choice by drawing on the concept of reflexive habitus – how individuals in contemporary society habitually negotiate choices around consumption, lifestyle and identity. We explore accounts of non-drinking choices through semi-structured interviews with 50 young people aged 16–19 from Melbourne, Australia, who either abstained from alcohol or drank minimally. Participants were encouraged to discuss how they had decided to either not drink or drink only lightly, and why they thought consumption practices among young people have changed. Their accounts centred on themes of (a) reflexively managing risk and health through non-drinking, (b) attempting to perform autonomy and self-expression through drinking choices, and (c) cultural politics: thinking reflexively about alcohol's role in society. Participants were conscious that consuming alcohol might influence their wellbeing, social functioning, and their sense of individuality, and were critical of constructions of alcohol as an expected feature of socialising. The growing pluralism of lifestyle choices and increasing structural and discursive pressures on young people may have encouraged a more reflexive habitus, in turn necessitating active choice-making about consumption practices that appears to be at odds with the cultural logic of heavy drinking.